(3GdCOhjI GdeaQOI aj GdfHGJs - (3GdZGabj , CMeO Hf eMeO Hf CMeO Hf GdSjO CHh LYaQ,J (B560 (3g` s
(3ChdgG (B:s
(3bGd CHh LYaQ CMeO Hf eMeO GdZGabi (B: (3bO cfJ TQYJ ai hVY cJGH ai GdCOhjI GdeaQOI CJNPJg JPcQI dfaSi s
(3BNQgG (B:s
(3hjSei MH GdRde , hgh GdeYQha YfOfG Hadad GdShOGf jRQY YfOfG RQYkG , hCcKQ fHGJg HHdGO GdShOGf , hgh HQi YfOge s
(3GdSaQ GdChd hgh fUa GdcJGHs
(3hGSJhai PcQ GdCOhjI GdJi PcQgG LGdjfhS hOjSbhQjOSs
(3hef LGA HYOgeGs
(3eQJH JQJjHkG CHLOjG hcd HGH bSeGf (B: (3bSe ai GdcdGe Yf GdCOhjI hGdBNQ ai TQM GdCSeGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B159 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B162s
Keywords: (3GdWHs